(untitled) (Research, Society and Development, 2022)
• Objective: To highlight the importance of the father’s participation in the prenatal and birth follow-up, thus contributing to the understanding of Fatherhood. Methodology: Descriptive quantitative research, field research, with men graduating from the nursing course aged between 18 and 40 years, Opinion No.: 4,507,103. Results: Although there are health programs created specifically for men, and the participants are future health professionals, many of them were unaware of the rights of paternity. Only 46% had knowledge about male prenatal care and its benefits, and few accompanied their wives in prenatal consultations. It is believed that parents need to be sensitized by the health team and improve their participation and knowledge on the subject. And also that the undergraduate curriculum needs to contemplate this subject more. Conclusion: Male prenatal care needs to be discussed more in the media, universities and health units, and nurses should welcome and sensitize parents to the importance of care during pregnancy, childbirth and the postpartum period.